Intent vs. action: talented employees and leadership development. Issue 2 (2nd March 2015) - Khoreva, Violetta; Vaiman, Vlad
Abstract : Purpose: – The purpose of this paper is to investigate the responses of employees, who are identified as talents by their multinational enterprises, in regards to leadership development activities. By applying social exchange and expectancy theories, the authors examine the association between talent identification, perceived effectiveness of leadership development activities, willingness to participate in those activities and actual participation in them. Design/methodology/approach: – The data were collected through a web-based questionnaire entitled "Leadership2020 Talent Survey". Eight multinational enterprises joined the survey and delivered a sample based on the target group definition. Findings: – The analysis shows that perceived effectiveness of leadership development activities is positively associated with willingness of employees to undertake those activities. The results also reveal that there is no significant association between the employees' willingness to participate in leadership development activities and their actual participation in those activities. Research limitations/implications: – Given its cross-sectional nature, the authors cannot completely exclude the possibility of common method bias having impact on the results of this study. The authors thus call for longitudinal research to examine the nature of causality within the relationships analyzed in this study. Practical implications: – Managers and practitioners should keep in mind that willingness to participate in leadership development activities does not always result in actual participation of employees in those activities. Symbolic representations may be very different from representations in real-life situations. Investigations that rely on the willingness as a proxy for actual behaviour must thus be interpreted with caution. Originality/value: – The authors found that employees often fail to act in accordance with their stated eagerness. According to the findings, there is a clear discrepancy between expressed willingness to implement certain behaviour and its actual implementation. This study poses a strong bias in overestimating the likelihood that an employee will engage in a desirable behaviour based on his/her willingness to do so.